Estimation of unknown function of nonlinear weakly singular integral inequalities of Gronwall–Bellman–Pachpatte type - Ran Yan; Fanwei Meng (Journal of Inequalities and Applications, 2019)
Abstract Some new nonlinear weakly singular integral inequalities of Gronwall–Bellman–Pachpatte type are given. The estimations of unknown functions are obtained by analysis techniques. These estimates are very significant tools in the study of differential-integral equations.